2006
DOI: 10.1111/j.1651-2227.2006.tb02262.x
|View full text |Cite
|
Sign up to set email alerts
|

Fever of unknown origin in 185 paediatric patients: A single‐centre experience

Abstract: Aim: We conducted a prospective study to evaluate the causes and outcome in children with fever of unknown origin (FUO). Methods: From 1990 to 1999, 185 children with FUO were evaluated. Initial evaluation included routine haematological analysis, Epstein‐Barr virus (EBV) serology, urine, stool or blood cultures, chest X‐ray and tuberculin probe. Results: In 131 (70%) patients diagnosis was established, and 70 (37.8%) had infectious disease. EBV infection was the most common infection followed by visceral leis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 13 publications
0
11
0
4
Order By: Relevance
“…Similar findings have been reported previously. [10][11][12][13] A recent study of children with FUO conducted by Cho et al in northern Taiwan, in which FUO was defined as fever for more than 2 weeks, found that infectious diseases accounted for 27% of FUO in children, followed by malignancies 16.6%, and collagen vascular disease 12.7%. Cho et al found that upper respiratory diseases (URI) were the most common cause of infectious disease, followed by CMV and EBV infection, and very rare caused by leptospirosis or scrub typhus.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar findings have been reported previously. [10][11][12][13] A recent study of children with FUO conducted by Cho et al in northern Taiwan, in which FUO was defined as fever for more than 2 weeks, found that infectious diseases accounted for 27% of FUO in children, followed by malignancies 16.6%, and collagen vascular disease 12.7%. Cho et al found that upper respiratory diseases (URI) were the most common cause of infectious disease, followed by CMV and EBV infection, and very rare caused by leptospirosis or scrub typhus.…”
Section: Resultsmentioning
confidence: 99%
“…[10][11][12][13] The 4-stage protocol used in this study to investigate the etiology of FUO provides for a reasonably accurate establishment of a diagnosis. Stage 2 of the protocol was sufficient to establish a diagnosis of infectious disease as the cause of FUO in most patients in this study.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…[6] The 18 included studies published from 1968 to 2008 consisted of 8 studies (all more than a decade old) from only 3 developed countries (Germany, USA and Spain) and 10 studies from developing countries ( Table 1). [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] The number of children in each case series varied from 10 to 221 (median 89.5) for a total of 1638 children (770 males; 628 females; 240 unknown). Definitions of FUO varied widely.…”
Section: Resultsmentioning
confidence: 99%
“…Tunisia 2006 [18] Fever >17 days for kids between 2 and 15 yrs 110 3 (3%) 8 (7%) 9 (8%) 64 (58%) 26 (24%) Serbia 2006 [19] Fever >3 weeks with temperature >38.3°C & no diagnostic signs or symptoms 185 12 (6%) 24 (12%) 25 (14%) 70 (38%) 54 (29%)…”
Section: Developing Countriesmentioning
confidence: 99%
“…Pasic et al [19] prospectively investigated the causes and outcome of childhood fever of unknown origin (FUO) in 185 patients referred to a single tertiary-care pediatric center in Belgrade, Serbia and Montenegro. Etiological cause was established in 71% and 38% had infectious diseases.…”
Section: Epidemiologymentioning
confidence: 99%